Merefleksikan Prinsip dan Tanggung Jawab Kepemimpinan Adam dalam Kepemimpinan Kristen: Kajian Biblis Kejadian 2-3 - Yonathan Salmon Efrayim Ngesthi; Carolina Etnasari Anjaya; Yonatan Alex Arifianto (JURNAL TERUNA BHAKTI, 2021)
The main task in Christian leadership is to guide, direct and educate God's people so that they can experience eternal salvation. This study outlines the discussion of Adam's leadership that ignores responsibility as God's chosen leader based on an analysis of the books of Genesis 2 and 3. The purpose of this study is to identify Adam's leadership points and describe the reflection of that leadership for today's church leaders. The method used is descriptive qualitative with an interpretive approach to the biblical text of Genesis 2-3. The results of the study found that the attitude of responsibility became the main point in carrying out Christian leadership duties so that they were in accordance with the truth of God's word. The attitude of responsibility contains several important points, namely: the first point, the responsibility for self-awareness as the holder of God's mandate. The second point is the responsibility to maintain, supervise and guide the people to follow God's decrees. The third point is the responsibility to maintain continuous interaction with God so that decisions and actions are based on God's wisdom alone. The fourth point is a responsibility as a living example. The fifth point, is the responsibility of continuous repentance and introspection.AbstrakTugas terutama dalam kepemimpinan Kristen adalah membimbing, mengarahkan dan mendidik umat Tuhan agar dapat mengalami keselamatan kekal. Penelitian ini menguraikan pembahasan tentang kepemimpinan Adam yang mengabaikan tanggung jawab sebagai pemimpin pilihan Tuhan didasarkan pada analisis kitab kejadian 2 dan 3.  Tujuan penelitian adalah mengidentifikasi poin-poin kepemimpinan Adam dan memaparkan refleksi dari kepemimpinan tersebut bagi para pemimpin jemaat masa kini. Metode yang dipergunakan adalah deskriptif kualitatif dengan pendekatan interpretasi terhadap teks Alkitab Kejadian 2-3.  Hasil penelitian menemukan bahwa sikap tanggung jawab menjadi poin utama dalam menjalankan tugas kepemimpinan Kristen agar sesuai dengan kebenaran firman Tuhan. Sika tanggungj jawab tersebut memuat beberapa poin penting yaitu: poin pertama, tanggung jawab kesadaran diri sebagai pemegang amanat Tuhan. Poin kedua, tanggung jawab menjaga, mengawasi dan membimbing umat untuk mengikuti ketetapan Tuhan. Poin ketiga, tanggung jawab memelihara interaksi dengan Tuhan secara terus menerus sehingga keputusan dan tindakan berdasarkan hikmat Tuhan semata. Poin keempat, tanggung jawab sebagai teladan yang hidup. Poin kelima, tanggung jawab pertobatan terus menerus dan mawas diri.